Implementation of a Mamdani Fuzzy-Based Decision Support System for Determining Social Assistance Priorities - Muslim Alamsyah; Mochammad Firman Arif (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Determining the priority of social assistance recipients is a semi-structured problem commonly faced by village governments and social institutions. The manual and subjective selection process often leads to mistargeting and inequitable distribution of aid. This study aims to implement a Decision Support System (DSS) based on the Mamdani Fuzzy method to determine the priority of social assistance recipients. The research object is data on prospective social assistance recipients in Sidowayah Village, Beji District, Pasuruan Regency. The criteria used include income, number of dependents, housing conditions, and employment status. The Mamdani Fuzzy method was selected because it effectively handles uncertainty and linguistic data in the decision-making process. The results demonstrate that the developed system can produce objective, consistent, and adaptive priority rankings for social assistance recipients compared to manual methods and the SAW method. Expert validation through interviews with village officials indicates that the system is deemed feasible for implementation, rated as valid to highly valid.